Studi Kasus Depresi Pada Siswa Akibat Perasaan Ditinggalkan Teman Sebaya Di SMA Bunda Hati Kudus Jakarta - Winarni Winarni; Erni Murniarti; Dameria Sinaga (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Adolescence is a developmental period in which peer relationships influence identity formation and emotional well-being. This study aims to describe psychological pressure leading to depressive symptoms in a secondary school student who felt abandoned by peers and to identify the factors and support provided by the school and family. This research used a qualitative case study approach involving one student at SMA Bunda Hati Kudus Jakarta. Data were collected through interviews with the student, parents, homeroom teacher, school counselor, and peers, as well as observation and home visit. The data were analyzed through data reduction, data display, and conclusion drawing, with triangulation used to strengthen credibility. The results show that feelings of being abandoned by peers, low problem-solving ability, and overprotective parenting contributed to social withdrawal, decreased school attendance, and loss of learning motivation. Supportive counseling, home visits, coordination between school and family, and gradual school reintegration helped the student regain emotional security. This study highlights the importance of early detection of students’ mental health problems and collaborative support in schools.